Nutrition and frailty - Lochlainn, Mary Ni (2021)
Funding Information: Acknowledgments: M.N.L. is supported by an NIHR Doctoral Fellowship (grant code NIHR300159). D.W. is supported by a NIHR Clinical Lectureship. A.A.S., A.G., C.H., P.H., S.R. and M.D.W. acknowledge support from the NIHR Newcastle Biomedical Research Centre. C.J.S. receives funds from the M.R.C., Wellcome Trust, Chronic Disease Research Foundation. E.R.T. is supported by the Medical Research Council (MRC) and Versus Arthritis as part of the Medical Research Council Versus Arthritis Centre for Integrated Research into Musculoskeletal Ageing (CIMA) [MR/R502182/1]. Funding Information: Importantly, nutrition represents a modifiable risk factor for frailty, and as such, is a target for both prevention and treatment of this debilitating syndrome. However, to design effective dietary interventions, a clearer understanding of the key dietary components and underlying mechanisms of action are needed. Progress in understanding the role and importance of nutrition and to address how diet can be used for the prevention and treatment of frailty, requires a multi-disciplinary approach. This review evolved from a workshop held on 6 November 2020, which was attended by all authors. The workshop was one of a series funded by the Medical Research Council under the UK Nutrition Research Partnership (UK NRP) Call for Nutrition Hot Topic Workshops. It brought together a new group of experts from the fields of nutrition and frailty, from a variety of backgrounds, in order to promote dialogue to address the potential of diet within strategies to prevent and treat frailty. The workshop had two aims: firstly, to review the evidence and current understanding of the links between nutrition and frailty, and secondly, to consider the gaps in the evidence and identify unanswered questions. Funding Information: We would like to acknowledge the Medical Research Council for their support in funding the workshop which led to the production of this paper, as part of the UK Nutrition Research Part-nership (UK NRP) Call for Nutrition Hot Topic Workshops.Acknowledgments: M.N.L. is supported by an NIHR Doctoral Fellowship (grant code NIHR300159). D.W. is supported by a NIHR Clinical Lectureship. A.A.S., A.G., C.H., P.H., S.R. and M.D.W. acknowledge support from the NIHR Newcastle Biomedical Research Centre. C.J.S. re-ceives funds from the M.R.C., Wellcome Trust, Chronic Disease Research Foundation. E.R.T. is supported by the Medical Research Council (MRC) and Versus Arthritis as part of the Medical Research Council Versus Arthritis Centre for Integrated Research into Musculoskeletal Ageing (CIMA) [MR/R502182/1]. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Copyright: Copyright 2021 Elsevier B.V., All rights reserved.